Development of multiple-representation based E-LKPD to improve students' scientific reasoning in classification of living things - Mahardika, I Ketut; Subchan, Wachju; Rosida, Rina Fatiya (STKIP Persada Khatulistiwa Sintang, 2024)
Scientific reasoning is a 21st-century skill that needs to be trained to prepare students to face the challenges of globalization. This can be supported by developing e-LKPD (electronic student worksheets) based on multiple representations. This research aims to determine the validity, practicality, and effectiveness of e-LKPD. This type of research is development research that applies the ADDIE model. The validation results by three experts had an average score of 81.66, 86.4, and 85.33 with a very valid category. Practical results were obtained based on student response questionnaires and observations of learning implementation. On a small scale at SMPN 2 Tanggul it was 78 (practical) and observation results were 87.11 (very practical), while on a class scale at SMPN 1 Wonosari, the student response questionnaire score was 81.28 (very practical) and observation results were 84.10 (very practical) practical), SMPN 1 Arjasa with a questionnaire response was 78.9 (practical) and observation results were 86.12 (very practical), MTsN 3 Banyuwangi was 87.72 (very practical) and observation results were 89.23 (very practical).